ACRYLIC EMULSION - COTTON CELLULOSE AND SYNTHETIC FIBRE COMPOSITE PAPER ADHESIVE (Journal of Pharmaceutical Negative Results, 2022)
To give the paper the necessary mechanical strength, an acrylic emulsion is used as a polymer spacer. Its use leads to increased mechanical strength, which indicates the formation of new hydrogen inter-molecular bonds. In order to clarify the mechanism of interaction of synthetic polymers with fibrous components of paper and to determine the structure of the resulting composition, infrared spectroscopic and X-ray crystallography studies were conducted.